Behavioral and neuropsychiatric challenges across the lifespan in individuals with Rubinstein-Taybi syndrome - Qu’d, Dima; Schmitt, Lauren M.; Leston, Amber; Harris, Jacqueline R.; Slavotinek, Anne; Riddle, Ilka; Brightman, Diana S.; Simpson, Brittany N. (Frontiers in Genetics, 2023)
Rubinstein-Taybi syndrome (RSTS) is a rare congenital disorder characterized by developmental and intellectual disability, broadening of thumbs and halluces, and dysmorphic facial features. Pathogenic variants in CREBBP lead to RSTS type 1 (RSTS1) and in EP300 lead to RSTS type 2 (RSTS2). Individuals with RSTS can demonstrate a variety of behavioral and neuropsychiatric challenges, including anxiety, hyperactivity/inattention, self-injury, repetitive behaviors, and aggression. Behavioral challenges are consistently reported as one of the primary factors impacting quality of life. Despite the high prevalence and morbidity of behavioral and neuropsychiatric features of RSTS, a paucity of data exists regarding its natural history. To better understand the neurocognitive and behavioral challenges faced by individuals with RSTS, 71 caregivers of individuals with RSTS, ranging in age from one to 61 years, completed four questionnaires measuring obsessive compulsive disorder (OCD)-like symptoms, anxiety, challenging behaviors, and adaptive behavior and living skills. Results revealed a high prevalence of neuropsychiatric and behavioral challenges across ages. We found specific challenging behaviors were worse in school age individuals. Scaled adaptive behavior and living skill scores differed across ages with an increased gap between typically developing peers becoming more apparent at older ages. Between types, individuals with RSTS2 had better adaptive behavior and living skills and less stereotypic behaviors but higher social phobia than individuals with RSTS1. However, both groups had impairments in adaptive functioning compared to typically developing peers. Our findings support and expand previous reports of a high prevalence of neuropsychiatric and behavioral challenges in individuals with RSTS. However, we are the first to report differences between types of RSTS. Further, age-related differences were seen with higher challenging behaviors within school-age individuals, which may improve over time and lower adaptive behavioral skills across ages. Anticipation of these potential differential challenges across age is vital for proactive management for individuals with RSTS. Our study underscores the importance of enacting neuropsychiatric and behavioral screening earlier in childhood so appropriate management can be implemented. However, further longitudinal studies in larger cohorts are needed to understand better how behavioral and neuropsychiatric characteristics of RSTS evolve over the lifespan and differentially affect subpopulation groups.